Social media marketing en marcas turísticas de El Oro. Caso: Playa Jambeli y Playa San Gregorio. - Cornejo Alvarez, Roger Joel; Vargas Chamba, Victor Manuel (My University, 2021)
Social networks are interaction platforms that make it possible to create a community around a brand, allowing followers to interact and interact immediately with the content they publish. In the current context, for tourism brands, social media marketing stands out as a fundamental tool for a managing online presence and maintaining notoriety in times of pandemic. Consequently, it is of interest to study how tourism brands use social media marketing to communicate with their audience and publicize their offer. The objective is to carry out a comparative analysis of the social media marketing strategies of Jambeli and San Gregorio beaches in the province of El Oro. The research is qualitative, the variables presence, engagement and publications were observed, bases on the PRGS model proposed by IAB Spain Research, but taking as a reference the adaptation of the same proposed by Gutiérrez, Sánchez and Galiano (2018). The results show that the social networks where tourism brands have great opportunities to be searched and found by users is Facebook. That the content strategies of tourism brands are dominated by promotional and branded content, in video and image format; identifying that the frequency, type of format and content have a direct impact on the participation or engagement rate.
Las redes sociales son plataformas de interacción que hacen posible crear una comunidad entorno a una marca propiciando que los seguidores se relacionen e interactúen de forma inmediata a partir del contenido que estas publican. En el contexto actual, para las marcas turísticas, el social media marketing destaca como una herramienta fundamental para gestionar la presencia online y mantener la notoriedad de en tiempos de pandemia. En consecuencia, es de interés estudiar cómo las marcas turísticas usan el social media marketing para comunicarse con su audiencia y dar a conocer su oferta. El objetivo es realizar un análisis comparativo de las estrategias de social media marketing de las playas Jambelí y San Gregorio de la Provincia de El Oro. La investigación es cualitativa, se observaron las variables presencia, engagement y publicaciones, a partir del modelo PRGS propuesto por IAB Spain Research, pero tomando como referencia la adaptación de la misma propuesta por Gutiérrez, Sánchez y Galiano (2018). Los resultados evidencian que la red social donde las marcas turísticas tienen grandes oportunidades de ser buscadas y encontradas por los usuarios, es Facebook. Que en las estrategias de contenidos de las marcas turísticas predominan los contenidos promocionales y de marca, en formato de video e imagen; identificando que la frecuencia, el tipo de formato y contenido tienen una incidencia directa sobre la tasa de participación o engagement.
Keywords: REDES SOCIALES; MARCAS TURÍSTICAS